Comprehensive income information: a user's perspective. (2015) - Durocher, Sylvain; Fortin, Anne
The goal of this experimental study was to examine whether nonprofessional investors actually use comprehensive income (CI) in their financial calculations and analyses. We assessed how these actors process actuarial gains and losses on defined benefit pension plans as an "other comprehensive income" (OCI) item, and whether the presentation format for CI affects their judgements and decisions, while considering the directional impact of the OCI item (actuarial loss or actuarial gain). Using 125 Canadian MBA students as proxies for nonprofessional investors, we conclude that nonprofessional investors generally do not use CI, are not affected by its presentation format, and are influenced in relatively few of their judgements by the direction of the OCI item's impact. These findings have important implications for standard setters, who may wish to better conceptualise the CI concept and revisit their current emphasis on CI information.